Verlossing as socio-politieke bevryding? - P. Robinson (Acta Theologica)
During the past two decades the theological debate on Biblical meaning of salvation has increased and intensified. Widely different approaches have developed of which the one extreme position sees salvation as "saving souls" in a clearly individualistic and spiritualistic way while on the other extreme one has the demand for total socio-political liberation. In order to understand this radicalizing of such a central Biblical concept as "salvation" one has to take note of some developments in theology and society during the 20th century. The mere development of a "Black" Theology in South Africa which holds this radical view of salvation must never be isolated from the existence of a "White" Theology which on its part holds a view of salvation that leaves society, despite its perversion, intact. The paper attempts to map these developments and test the two opposing views on salvation with what the Biblical tradition proclaims.